Chorangioma of placenta: single center analysis - Kochoska, Milka; Krsteska, Blagica; Kostadinova Kunovska, Slavica; Kochmanovska Petreska, Svetlana; Ristovski, Grigor; Risteski, Vladimir; Bajdevska Dukoska, Daniela; Petrushevska, Gordana; Milkovski, Daniel (Wiley, 2022)
Background: The most common benign neoplasms of the placenta are non-trophoblastic tumours. They include chorioangioma, teratoma, leiomyoma and hepatocellular adenoma. Chorioangioma is the most common subtype. The incidence of chorangioma is 0.5–1.0%. Small chorangiomas are clinically insignificant. Giant chorioangioma is rare tumours, measuring more than 4 cm in diameter and seen in association with elderly primi, twin pregnancy, hypertension, diabetics, and female fetus. Giant chorioangioma is associated with complications that can affect the mother, fetus, or neonate. Aims: This is a retrospective study of chorangioma cases seen at Institute of Pathology, Medical faculty, Skopje during a 10-year period from 2012 to 2021. Methods: Macroscopic findings, gestational weeks at delivery, maternal age and outcome of pregnancy were evaluated. Histological and immunochistochemical analyses of the placental chorangiomas were preformed. Results & Conclusions: In period of 10 years 6 causes of placental chorangioma were clinically identified and histopathologically confirmed. Four cases were giant chorangiomas measuring from 8 to 13 cm. One of the cases was identified as chorangioma of the umbilical cord. Three of the cases shows potential maternal risk factors like primary infertility, extreme obesity and post COVID status. The median gestational age of delivery was 33 + 6 weeks and 39.6 weeks, respectively. The maternal age range was between 25 to 34 years. Four of the pregnancies had favourable outcome with no complications during and after birth. One was with foetal distress and one with premature delivery. Microscopic examination of the mass showed numerous proliferative thin walled capillaries lined by f lattened endothelium and separated by fibrous stroma. This was further confirmed by IHC for CD34, which showed strong reactivity of endothelial cells.